The Transnational Return: Tracing the Spatial Politics of CanLit - Zacharias, Robert (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2016)
This essay considers the spatial politics of the transnational turn in recent Canadian literary criticism, historicizing the growth of explicitly spatial critical frames—diaspora studies, globalization, critical regionalism, new border studies—within the longer “topocentricism” of the field. Taking the rise of hemispheric criticism as a particularly charged case study, I suggest that the most common function of such work has been a transnational return, less a decisive move beyond the limits of the national frame than a complex extension of English-Canadian literary studies’ longstanding engagement with literary nationalism.